Control over size, shape, and photonics of self-assembled organic nanocrystals - Shahar, Chen; Tidhar, Yaron; Jung, Yunmin; Weissman, Haim; Cohen, Sidney R.; Bitton, Ronit; Pinkas, Iddo; Haran, Gilad; Rybtchinski, Boris (Beilstein Journal of Organic Chemistry, 2021)
The facile fabrication of free-floating organic nanocrystals (ONCs) was achieved via the kinetically controlled self-assembly of simple perylene diimide building blocks in aqueous medium. The ONCs have a thin rectangular shape, with an aspect ratio that is controlled by the content of the organic cosolvent (THF). The nanocrystals were characterized in solution by cryogenic transmission electron microscopy (cryo-TEM) and small-angle X-ray scattering. The ONCs retain their structure upon drying, as was evidenced by TEM and atom force microscopy. Photophysical studies, including femtosecond transient absorption spectroscopy, revealed a distinct influence of the ONC morphology on their photonic properties (excitation energy transfer was observed only in the high-aspect ONCs). Convenient control over the structure and function of organic nanocrystals can enhance their utility in new and developed technologies.
Keywords: aromatic amphiphiles; exciton diffusion; organic nanocrystals; perylene diimides; self-assembly